Disharmonisasi Norma Tanggung Jawab Pelaku Usaha Berbasis Strict Liability dalam Sengketa Konsumen - Ni Putu Mirah Henny Herliana; Dewa Ayu Putri Sukadana; Kadek Januarsa Adi Sudharma; Ni Putu Sawitri Nandari (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study examines the normative inconsistency in regulating business actors’ liability under Law No. 8 of 1999 on Consumer Protection, particularly in relation to the application of strict liability. The main problem arises from the coexistence of different liability regimes, namely strict liability, fault-based liability, and presumption of liability, without clear conceptual boundaries. This situation creates legal uncertainty and weakens the position of consumers. The research aims to analyze this inconsistency and propose a conceptual reconstruction to achieve legal coherence. This study applies a normative juridical method with statutory, conceptual, and analytical approaches, focusing on Articles 19(1), 19(5), and 28 of the law. The findings show that the overlap of liability models leads to ambiguity in interpretation and inconsistent law enforcement, which enables business actors to avoid responsibility. This condition is not in line with the principles of legal certainty and justice within the welfare state framework. Therefore, clearer differentiation of liability regimes is required through legislative clarification or judicial guidelines so that strict liability can function effectively in protecting consumers and ensuring fair business practices.